Training load, recovery and interval endurance in elite female soccer players - Brink, M.; Visscher, C.; Mol, J.; Lemmink, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In 2007, Dutch female soccer players kicked-off for the first time in a new national premier league. Goal of this premier league was to stimulate female soccer in the Netherlands and qualify for international tournaments. Therefore, training load increased tremendously. However, little is know about the training-performance relation in elite female soccer. The purpose of this study was to monitor load and recovery in relation to interval endurance capacity. Methods At the start of the season in 2007, thirteen elite female soccer players (mean ± SD: age 22.8 ± 4.31 (range 17-30) years, body weight 64.4 ± 10.7 kg and body fat 25.1 ± 3.14 %) performed two Interval Shuttle Run Tests (ISRT) with eight weeks in between (Lemmink, et al. 2004). During the ISRT, player alternately ran 30 seconds and walked 15 seconds, until exhaustion. The number of completed runs was registered as outcome of performance. Additional, heart rate was recorded at 5-s intervals (Polar, Kempele, Finland). By means of training logs, training and match duration (minutes), session-RPE and Total Quality Recovery (TQR) scores were collected (Kenttä et al. 1998). Training load was calculated by multiplying training and match duration with session-RPE. A paired samples t-test was used to test performance changes. Pearson`s correlation coefficients were used to relate training load and recovery to performance. Results: Average maximal heart rate was 193,6 ± 4,46 b•min-1 after the first and 191,9 ± 5,97 b•min-1 after the second ISRT. The female soccer players completed significantly more runs at the second ISRT (82.8 ± 10.8 runs) compared to the first (73.7± 8.1) (p<0.001). Average training and match duration was 349 ± 36 minutes per week. Average session-RPE and TQR scores were 13,3 ± 0,92 and 13.8 ± 1,2 respectively, indicating "somewhat hard" intensity and "reasonable to good" recovery. Improvement in endurance capacity was not significantly related to training load and recovery. Discussion: It can be concluded that interval endurance capacity improved during the first eight weeks of the season, but was not related to training load and recovery. This might be due to a relative long period between both tests (Brink et al. 2009). Since the training response depends on individual characteristics, the heterogeneity (i.e. wide range in age) of the group might as well disturb this relation. Based on these results coaches should more frequently execute field tests and evaluate the individual training response.